IMPLEMENTASI KEAMANAN FILE PADA APLIKASI PENYIMPANAN BERBASIS CLOUD COMPUTING DENGAN ALGORITMA ADVANCED ENCRYPTION STANDARD (AES) DAN KOMPRESI LEMPEL ZIV WELCH (LZW) - Dwi Setyo Wiratomo (2022)
Data files are data used by every company, organization, or individual. Moreover, important data is stored in the database. So that the data can be accessed flexibly, it can be stored in cloud storage. But security in cloud storage is not enough to avoid leaking data stored in cloud storage. By using Cryptography, the security of data stored in cloud storage will be layered and not easily retrieved or damaged by intruders. Although it is very easy to access, it must also be prepared for data security from cloud users. Every cloud service must provide secure data security for its users in order to avoid intruders to retrieve and destroy cloud user data. Cloud Storage is part of a cloud computing system that provides storage media that can be accessed only by requiring an internet network. There are several types of storage media that are developing, one of which is cloud-based storage media. Data security is important in cloud services. One of them is storage media that can be accessed under any circumstances and anywhere. Cryptographic techniques are one way to secure data stored in cloud services. One of the cryptographic techniques used is the Advanced Encryption Standard (AES) algorithm which will result in encryption and decryption of file data without changing the contents of the file and compressing files using the Lempel Ziv Welch (LZW) algorithm to reduce file size and speed up file delivery to the cloud storage.